Quantitative analysis of BGP convergence and its influence on network performance - ZHAO Jin-jing; ZHU Pei-dong; LU Xi-cheng (Tongxin xuebao)
The relation of BGP convergence and the characteristics of the inter-domain system was analyzed.The in-ter-domain routing system is classified into three hierarchies—core layer,transmit layer and stub layer based on the power law and commercial relations of autonomous systems.The relation of network topology and convergence parame-ters were presented of all sorts of convergence events in different layers.And a new proposal has been presented to im-prove BGP convergence based on the above analysis,called Best Up,which behaved better than normal convergence mode in the experiments.